Ethylene / α-olefin copolymer for solar cell encapsulation film and its application

By preparing an ethylene/α-olefin copolymer that meets specific conditions and combining it with crosslinking agents and other components, the balance between anti-PID performance and vulcanization reaction rate of solar cell encapsulation films was solved, achieving the effects of rapid vulcanization and excellent anti-PID performance.

CN118599045BActive Publication Date: 2025-01-10WANHUA CHEM GRP CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411079238.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-10-16
Filing Date
2024-08-07
Publication Date
2025-01-10
Estimated Expiration
2044-08-07

AI Technical Summary

Technical Problem

Existing solar cell encapsulation films struggle to achieve a good balance between PID resistance and vulcanization reaction rate, and existing improvement methods suffer from additive precipitation issues or problems affecting optical performance.

Method used

An ethylene/α-olefin copolymer is provided, which meets specific characteristics of relaxation time, weight-average molecular weight and molecular weight distribution. It is prepared by a dissolution-precipitation separation method and is used as an encapsulating film for solar cells. It combines crosslinking agents, co-crosslinking agents and coupling agents to form a dense crosslinked structure.

Benefits of technology

This technology enables rapid vulcanization of solar cell encapsulation films and excellent anti-PID performance, thereby improving the overall performance of the encapsulation films and the lifespan of the modules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention provides an ethylene / α-olefin copolymer for solar cell encapsulation film and its application. The ethylene / α-olefin copolymer provided by the present invention is used in the solar cell encapsulation film, which can take into account the faster vulcanization reaction speed and good anti-PID performance of the solar cell encapsulation film. The ethylene / α-olefin copolymer for solar cell encapsulation film satisfies the following conditions (a) to (c): (a) under the angular frequency condition of 0.1-500 rad / s, the characteristic relaxation time at 190°C is 200.0-500.0 milliseconds; (b) the weight average molecular weight is 20000-200000 g / mol, and the density is 0.850 g / cc to 0.910 g / cc; (c) the molecular weight distribution is 1.5-3.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solar cell encapsulation adhesive films, and in particular to an ethylene / alpha-olefin copolymer used for solar cell encapsulation adhesive films and applications thereof. Background Art

[0002] Photovoltaic power generation is one of the most competitive forms of new energy and is expected to expand rapidly in the future. The corresponding encapsulation film materials ethylene-vinyl acetate (EVA) and ethylene / α-olefin copolymer (POE) account for a small proportion of the total cost of photovoltaic modules, about 7%, but they are the key factors that determine the quality and life of photovoltaic modules. Once the film and backplane of the battery module begin to yellow and crack, the battery is likely to be scrapped prematurely. Photovoltaic modules work and use in high-voltage environments for a long time, and wet leakage current channels are easily generated between the encapsulation materials, backplanes, glass and frames. A large amount of charge accumulates on the surface of the battery cell, which makes the battery surface passivated significantly, resulting in a significant attenuation of the performance of the module, which is called the PID phenomenon.

[0003] At present, the mainstream means of achieving anti-PID film are: ① using polyolefin elastomer POE material with lower water permeability instead of EVA material; ② adding additional anti-PID additives to the formula. However, both of the above methods have disadvantages: the intrinsic anti-PID performance of POE film still needs to be improved; and the addition of inorganic additives will affect the optical properties of the film, thereby causing the haze of the film to increase. Patent application CN112898920A, patent application CN113234402A, and patent CN113122164B achieve the purpose of anti-PID of the film by adding inorganic and organic small molecule additives, but the introduction of additional additives is always accompanied by the problem of additive precipitation, which affects the long-term use performance of the encapsulation film. Patent application CN112824466A introduces additional co-crosslinking agents into the photovoltaic film formula system, so that the crosslinking density of the crosslinked encapsulation film is increased, thereby enhancing the barrier ability to metal ions, thereby achieving the anti-PID effect, but it still belongs to the optimization of the formula system, and the encapsulation material itself has not been improved.

[0004] Another important aspect is that based on the downstream film processing needs, how to improve the vulcanization speed of photovoltaic films, thereby shortening the processing time of lamination cross-linking reactions, and achieving greater cost reduction and efficiency improvement is an urgent problem to be solved in the industry. The existing solution to speed up the vulcanization speed of POE photovoltaic films is mainly to modify POE particles by formula optimization or by means of silane grafting. Patent application CN116023891A uses chemical grafting modification to graft silane monomers onto POE macromolecular chains to form a high molecular weight tackifier, thereby contributing to the cross-linking degree of film curing through silane cross-linking, increasing the cross-linking speed of the film and shortening the curing cycle. Patent application CN115873528A optimizes the film cross-linking formula to speed up the cross-linking speed and improve the production efficiency of the components. Patent application CN116004126A improves the cross-linking characteristics by changing the layer structure of the encapsulation film, and comprehensively improves the encapsulation effect of POE applied in components. Overall, there are few reports and applications using pure POE particles as a starting point to improve the cross-linking vulcanization speed and anti-PID performance of photovoltaic films.

[0005] In summary, it is very necessary to provide a solution that can achieve both faster vulcanization reaction speed and good anti-PID performance without upgrading the solar cell encapsulation film formula. Summary of the invention

[0006] The present invention provides an ethylene / α-olefin copolymer for solar cell encapsulation film and its application. The ethylene / α-olefin copolymer provided by the present invention is used in the solar cell encapsulation film, which can take into account both the faster vulcanization reaction speed of the solar cell encapsulation film and good anti-PID performance.

[0007] To achieve the purpose, the present invention provides the following technical solutions:

[0008] In one aspect, the present invention provides an ethylene / α-olefin copolymer for solar cell encapsulation film, wherein the copolymer satisfies the following conditions (a) to (c):

[0009] (a) The characteristic relaxation time at 190 °C is 200.0–500.0 ms at an angular frequency of 0.1–500 rad / s.

[0010] (b) a weight average molecular weight of 20,000 to 200,000 g / mol and a density of 0.850 g / cc to 0.910 g / cc;

[0011] (c) Molecular weight distribution is 1.5-3.

[0012] Preferably, the characteristic relaxation time is 350.0-500.0 milliseconds, more preferably 400-500 milliseconds.

[0013] Furthermore, the copolymer has a melt index of 1 g / 10 min to 50 g / 10 min at 190° C. and 2.16 kg load.

[0014] In some embodiments, the weight average molecular weight is 40,000-100,000 g / mol.

[0015] In some embodiments, the α-olefin includes one or more of propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, and 1-eicosene.

[0016] The second aspect of the present invention provides a method for preparing the ethylene / α-olefin copolymer for solar cell encapsulation film, the method comprising the following steps:

[0017] (S1) polymerizing ethylene and α-olefin to obtain a copolymer product;

[0018] (S2) post-treating the copolymerization product to separate therefrom an ethylene / α-olefin copolymer that satisfies conditions (a) to (c):

[0019] (a) under the condition of angular frequency of 0.1-500 rad / s, the characteristic relaxation time at 190°C is 200.0-500.0 milliseconds, preferably 350.0-500.0 milliseconds, more preferably 400-500 milliseconds;

[0020] (b) a weight average molecular weight of 20,000 to 200,000 g / mol and a density of 0.850 g / cc to 0.910 g / cc;

[0021] (c) Molecular weight distribution is 1.5-3.

[0022] The third aspect of the present invention provides a solar cell encapsulation adhesive film composition, wherein the composition comprises the above-mentioned ethylene / α-olefin copolymer or the ethylene / α-olefin copolymer prepared by the above-mentioned preparation method.

[0023] Furthermore, the composition also contains one or more of a cross-linking agent, a co-cross-linking agent, a coupling agent and an antioxidant.

[0024] A fourth aspect of the present invention provides a solar cell encapsulation adhesive film, which is prepared by using the composition.

[0025] The fifth aspect of the present invention provides a method for preparing the solar cell encapsulation film, comprising the following steps:

[0026] The components in the composition are mixed and melted, extruded and cast into a film, and then cooled and cut.

[0027] A sixth aspect of the present invention provides a solar cell assembly, which comprises the solar cell encapsulation film.

[0028] The technical solution provided by the present invention has the following beneficial effects:

[0029] The ethylene / α-olefin copolymer for solar cell encapsulation film provided by the present invention satisfies the above conditions (a) to (c) at the same time and has a higher characteristic relaxation time. The copolymer can enable the solar cell encapsulation film to have both a faster vulcanization reaction speed and good anti-PID performance. DETAILED DESCRIPTION

[0030] In order to facilitate the understanding of the present invention, the present invention will be further described below in conjunction with examples. It should be understood that the following examples are only for a better understanding of the present invention and do not mean that the present invention is limited to the following examples.

[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the invention belongs. The term "and / or" as may be used herein includes any and all combinations of one or more of the associated listed items.

[0032] Where specific experimental steps or conditions are not specified in the examples, the corresponding conventional experimental steps or conditions in the art can be used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be purchased commercially.

[0033] The ethylene / α-olefin copolymer for solar cell encapsulation film provided by the present invention satisfies the following conditions (a) to (c) at the same time:

[0034] (a) The characteristic relaxation time at 190 °C is 200.0–500.0 ms at an angular frequency of 0.1–500 rad / s.

[0035] (b) a weight average molecular weight of 20,000 to 200,000 g / mol and a density of 0.850 g / cc to 0.910 g / cc;

[0036] (c) Molecular weight distribution is 1.5-3.

[0037] The ethylene / α-olefin copolymer for solar cell encapsulation film of the present invention has the following characteristics (a): under the angular frequency condition of 0.1-500 rad / s, the characteristic relaxation time at 190°C is greater than or equal to 200.0 milliseconds and less than or equal to 500.0 milliseconds, for example, 200.0 milliseconds, 250.0 milliseconds, 300.0 milliseconds, 350.0 milliseconds, 400.0 milliseconds, 450.0 milliseconds, 500.0 milliseconds, etc.; preferably, the characteristic relaxation time is 350.0-500.0 milliseconds, more preferably 400-500 milliseconds.

[0038] The ethylene / α-olefin copolymer for solar cell encapsulation film of the present invention has the characteristics of the above-mentioned characteristic relaxation time and also has the following characteristics (b) and (c): (b) a weight average molecular weight of 20000-200000 g / mol and a density of 0.850 g / cc to 0.910 g / cc; (c) a molecular weight distribution of 1.5-3.

[0039] The use of ethylene / α-olefin copolymers having the above characteristics (a)-(c) to prepare solar cell encapsulation films can achieve both a shorter vulcanization reaction time and good anti-PID performance.

[0040] The ethylene / α-olefin copolymer for solar cell encapsulation film provided by the present invention has a weight average molecular weight (M w ) is 20000-200000 g / mol, for example 40000-100000 g / mol, for example 40000-90000 g / mol, further for example 45000-75000 g / mol.

[0041] The ethylene / α-olefin copolymer for solar cell encapsulation film provided by the present invention has a density of 0.850 g / cc to 0.910 g / cc, for example, 0.850 g / cc, 0.860 g / cc, 0.870 g / cc, 0.880 g / cc, 0.890 g / cc, 0.900 g / cc, 0.905 g / cc, 0.910 g / cc, etc.

[0042] The ethylene / α-olefin copolymer for solar cell encapsulation film provided by the present invention has a molecular weight distribution (PDI) of 1.5-3, such as 1.5, 1.8, 2.0, 2.2, 2.4, 2.6, 2.8, etc., and further such as 2.1-2.8.

[0043] In addition, the ethylene / α-olefin copolymer for solar cell encapsulation film provided by the present invention may have a melt index (MI) of 1 g / 10min to 50 g / 10min at 190°C and 2.16 kg load, such as 1 g / 10min, 2 g / 10min, 3 g / 10min, 5 g / 10min, 10 g / 10min, 15 g / 10min, 17 g / 10min, 20 g / 10min, 25 g / 10min, 30 g / 10min, 40 g / 10min, 45 g / 10min, 50 g / 10min, etc., such as 2 g / 10min to 40 g / 10min, such as 2 g / 10min to 20 g / 10min, and further such as 3 g / 10min to 17 g / 10min.

[0044] The ethylene / α-olefin copolymer of the present invention may be a random or block polymer, wherein the α-olefin is derived from an α-olefin as a comonomer, and the α-olefin may include, for example, a mixture of one or more of propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene and 1-eicosene.

[0045] Characteristic Relaxation Time refers to the time it takes to restore the equilibrium state of stress in a polymer after a constant deformation is applied to the polymer. The characteristic relaxation time is related to the entanglement structure of the polymer chain. If the polymer has long chain branches, as the branched structure increases, the degree of chain entanglement increases, which leads to a longer characteristic relaxation time of the polymer. At the same time, as the degree of chain entanglement increases, the free volume of the polymer chain increases, so that this part of the polymer is more susceptible to solvation in the solvent, thereby enhancing the solubility. Therefore, it has the ability to separate in actual production applications, that is, a polymer with target characteristics can be obtained by dissolution-precipitation-separation.

[0046] The present invention also provides a method for preparing the ethylene / α-olefin copolymer for solar cell encapsulation film. The ethylene / α-olefin copolymer provided by the present invention can be prepared by a preparation method comprising the following steps: (S1) polymerizing ethylene and α-olefin to obtain an ethylene / α-olefin copolymer product; (S2) post-treating the copolymer product to separate therefrom an ethylene / α-olefin copolymer that satisfies conditions (a) to (c) at the same time:

[0047] (a) under the condition of angular frequency of 0.1-500 rad / s, the characteristic relaxation time at 190°C is 200.0-500.0 milliseconds, preferably 350.0-500.0 milliseconds, more preferably 400-500 milliseconds;

[0048] (b) a weight average molecular weight of 20,000 to 200,000 g / mol and a density of 0.850 g / cc to 0.910 g / cc;

[0049] (c) Molecular weight distribution is 1.5-3.

[0050] In some embodiments, the step (S2) of post-treating the copolymerization product specifically comprises the following steps:

[0051] (S2a) The obtained copolymer product is first dissolved in a first good solvent, and then the obtained solution is added to a first poor solvent for precipitation separation to obtain a first liquid phase portion, and the solvent in the first liquid phase portion is removed to obtain the desired product. Further, step (S2b) can also be performed: the precipitate portion obtained by precipitation separation in step (S2a) is dissolved in a second good solvent, and then the obtained solution is added to a second poor solvent for precipitation separation to obtain a second liquid phase portion, and the solvent in the second liquid phase portion is removed to obtain the desired product.

[0052] Step (S1):

[0053] Step (S1) is a step of preparing an ethylene / α-olefin copolymer product by polymerizing ethylene and α-olefin.

[0054] In step (S1), solution polymerization can be specifically used. As a reference example, step (S1) may include the following steps: in a reactor, an organic solvent and α-olefin are fed into the reactor by solution polymerization, a main catalyst and a co-catalyst are added to the reactor at a desired reaction temperature, and ethylene gas is fed into the reactor for reaction to obtain a reactant solution; wherein the polymerization monomer (α-olefin and / or ethylene) can be fed in one or more steps to control polymer index parameters, such as weight average molecular weight, molecular weight distribution, α-olefin copolymer content, etc.; after removing the solvent from the obtained reactant solution, an ethylene / α-olefin copolymer product is obtained. Among them, the reactor used can be a reactor conventionally used in the art, such as a ring reactor, an isothermal reactor, a stirred tank reactor, an intermittent reactor, a circulating tubular reactor, etc. The reactor may include one or more reactors in parallel, in series, and / or in any other combination; the reaction may be carried out in a continuous or intermittent manner.

[0055] Furthermore, the organic solvent used for the polymerization reaction in step (S1) may be one or more of an aliphatic solvent and an aromatic solvent. Preferably, the aliphatic solvent is selected from one or more of n-butane, isobutane, n-pentane, cyclopentane, n-hexane, cyclohexane, n-heptane, n-octane, n-nonane and their alkylated compounds. Preferably, the aromatic solvent is selected from one or more of benzene, toluene, xylene and their halogenated compounds, wherein the halogenated compound may be a monohalogenated compound or a polyhalogenated compound.

[0056] Further, the main catalyst used for the polymerization reaction in step (S1) is preferably one or more of a metallocene catalyst and a post-metallocene catalyst, preferably one or more of dimethylsilyl tert-butylamine tetramethylcyclopentadiene titanium dichloride, bis(methylcyclopentadiene) zirconium dichloride, bis(1,3-dimethylcyclopentadienyl) zirconium dichloride, cyclopentadienyl-(1,2-dimethoxyethane) zirconium trichloride, and dimethylsilyl bis(2-methyl-4-phenylindenyl) zirconium dichloride. Those skilled in the art can determine the specific amount of the main catalyst according to the reaction requirements. For example, in some embodiments, the amount of the main catalyst can be 1-20 μmol / L relative to the amount of the reaction system solvent.

[0057] Furthermore, the co-catalyst used for the polymerization reaction in step (S1) is preferably at least one of alkyl aluminum, organic boron compound, and alkyl aluminoxane, preferably one or more of methyl aluminoxane, modified methyl aluminoxane, ethyl aluminoxane, trimethyl aluminum, triethyl aluminum, triisobutyl aluminum, and tris (pentafluorophenyl) boron compound. The molar ratio of aluminum in the co-catalyst to the main catalyst metal atom can be 1 to 1000:1, and the molar ratio of boron in the co-catalyst to the main catalyst metal atom can be 0 to 5:1.

[0058] Furthermore, in step (S1), the reaction temperature is, for example, 100-210° C., such as 120-210° C., and the reaction pressure is, for example, 20-100 bar.

[0059] Step (S2a) and Step (S2b):

[0060] Step (S2a) and step (S2b) are steps of post-treating the ethylene / α-olefin copolymer product obtained in step (S1) to obtain the ethylene / α-olefin copolymer for solar cell encapsulation film provided by the present invention.

[0061] In step (S2a), the first good solvent used refers to a solvent that can completely dissolve the copolymer product in step (S1). In step (S2b), the second good solvent used refers to a solvent that can completely dissolve the precipitate obtained in step (S2a). Specifically, the first good solvent and the second good solvent can be one or more of an aliphatic solvent and an aromatic solvent, respectively. Preferably, the aliphatic solvent is selected from one or more of n-butane, isobutane, n-pentane, cyclopentane, n-hexane, cyclohexane, n-heptane, n-octane, n-nonane and their alkylated compounds. Preferably, the aromatic solvent is selected from one or more of benzene, toluene, xylene and their halogenated compounds, wherein the halogenated compound can be a monohalogenated compound or a polyhalogenated compound. The dissolution operation using the first good solvent or the second good solvent can be carried out at 60-140°C, and the dissolution operation can be carried out under stirring; when the first good solvent is used for dissolution, the mass ratio of the copolymer product to the solvent is, for example, 1:3 to 1:8; when the second good solvent is used for dissolution, the mass ratio of the above-mentioned precipitate to the solvent is, for example, 1:3 to 1:8.

[0062] In step (S2a), the first poor solvent used can be an alcohol having 2-20 carbon atoms. Preferably, it is a mixture of one or more of ethanol, ethylene glycol, n-propanol, glycerol, n-butanol, neopentyl alcohol, 1,6-hexanediol, n-octanol, n-decanol, dodecanol, tetradecanol, and hexadecanol. The amount of the first poor solvent used can be 1-5 times the mass of the first good solvent in which the polymer is completely dissolved. The conditions for precipitation separation with the first poor solvent can be, for example, at room temperature or 18-22°C, in a solution in which the first good solvent in which the polymer is completely dissolved, gradually adding the first poor solvent, and continuously stirring (for example, at a speed of 200-400 rpm) until no polymer precipitates in the solution. After that, the polymer precipitate in the solution is filtered and separated, and then the solution is partially evaporated to remove the solvent to obtain the ethylene / α-olefin copolymer for solar cell encapsulation film provided by the present invention.

[0063] The second poor solvent used in step (S2b) can be a mixed solution of an alcohol solvent and a ketone solvent. The alcohol solvent can be an alcohol having 2-20 carbon atoms, preferably a mixture of one or more of ethanol, ethylene glycol, n-propanol, propylene glycol, n-butanol, neopentyl alcohol, 1,6-hexanediol, n-octanol, n-decanol, dodecanol, tetradecanol, and hexadecanol. The ketone solvent is preferably a mixture of one or more of dimethyl ketone, diethyl ketone, butanone, methyl isobutyl ketone, valerophenone, 3-methyl-2-octanone, methyl nonanone, methyl hexanophenone, bicyclo[3.3.1]nonane-3,7-dione, dimethylcyclohexanedione, 2,2,6-trimethyl-1,4-cyclohexanedione, diphenylethanedione, 3-methyl-2,4-nonanedione, 1-phenyl-2,4-pentanedione, and 2,4-decanedione. Preferably, the mass ratio of alcohol solvent to ketone solvent can be 4-10:1; the amount of the second poor solvent can be 1-5 times the mass of the second good solvent in which the polymer is completely dissolved. In step (S2b), the precipitation separation condition can be room temperature, or 18-22°C, in the solution in which the second good solvent in which the polymer is completely dissolved, gradually add the second poor solvent, and continue stirring (for example, the speed is 200-400 rpm) until no polymer precipitates in the solution. After that, the polymer precipitate in the solution is filtered and separated, and then the solution is partially evaporated to remove the solvent to obtain the ethylene / α-olefin copolymer for solar cell encapsulation film provided by the present invention.

[0064] By treating the precipitated portion of step (S2a) through step (S2a) or through step (S2b), the ethylene / α-olefin copolymer for solar cell encapsulation film of the present invention satisfying conditions (a) to (c) can be obtained.

[0065] The present invention also provides a solar cell encapsulation film composition, which contains the ethylene / α-olefin copolymer for solar cell encapsulation film or the ethylene / α-olefin copolymer for solar cell encapsulation film prepared by the preparation method. Specifically, the ethylene / α-olefin copolymer satisfies the following conditions (a) to (c) at the same time:

[0066] (a) under the condition of angular frequency of 0.1-500 rad / s, the characteristic relaxation time at 190°C is 200-500 milliseconds, preferably 350.0-500.0 milliseconds, more preferably 400-500 milliseconds;

[0067] (b) a weight average molecular weight of 20,000 to 200,000 g / mol and a density of 0.850 g / cc to 0.910 g / cc;

[0068] (c) Molecular weight distribution is 1.5-3.

[0069] The specific contents of the ethylene / α-olefin copolymer in the above composition can be referred to the corresponding description of the ethylene / α-olefin copolymer for photovoltaic encapsulation film provided by the present invention in the above text, and will not be repeated here.

[0070] The above composition adopts the ethylene / α-olefin copolymer for photovoltaic encapsulation film provided by the present invention, which can significantly shorten its vulcanization reaction time and give the obtained encapsulation film excellent anti-PID performance.

[0071] The solar cell encapsulation film composition may also include other components conventionally added in the art, specifically, for example, one or more of a crosslinking agent, a co-crosslinking agent, a coupling agent, and an antioxidant. Of course, other additional components allowed to be added in the art may also be included.

[0072] Further, the cross-linking agent can be a peroxide cross-linking agent, including but not limited to a combination of one or more of the following compounds: tert-butyl peroxy isopropyl carbonate, 2,5-dimethyl-2,5-(bis-tert-butylperoxy)hexane, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, 2,2-bis(tert-butylperoxy)butane, tert-butyl peroxy 2-ethylhexyl carbonate, tert-amyl peroxy carbonate, tert-butyl peroxy 3,3,5-trimethylhexanoate. The crosslinking agent may be used in an amount of 0.1 to 5 parts by weight, preferably 0.5 to 2 parts by weight, based on 100 parts by weight of the ethylene / α-olefin copolymer.

[0073] Further, the auxiliary crosslinking agent can be a combination of one or more of multifunctional acrylate substances, including but not limited to a combination of one or more of the following substances: triallyl isocyanurate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, tris(2-hydroxyethyl)isocyanuric acid triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, ethoxylated glycerol triacrylate, propoxylated glycerol triacrylate, pentaerythritol tetrapropylene glycol ... The crosslinking aid may be used in an amount of 0.1-5 parts by weight, preferably 0.1-2 parts by weight, based on 100 parts by weight of the ethylene / α-olefin copolymer.

[0074] Further, the coupling agent can be a silane coupling agent, including but not limited to a combination of one or more of the following compounds: γ-methacryloxypropyl trimethoxysilane, γ-chloropropyl methoxysilane, vinylethoxysilane, γ-(2,3-epoxypropoxy)propyl trimethoxysilane, vinyl tri(β-methoxyethoxy)silane, γ-methacryloxypropyl trimethoxysilane, vinyl triacetoxysilane, γ-glycidyl ether oxygen propyl trimethoxysilane, 3-(trimethoxysilyl)propyl-2-methyl-2-acrylate, aniline methyl triethoxysilane, octyl trimethoxysilane. Based on 100 parts by weight of ethylene / α-olefin copolymer, the amount of the coupling agent can be 0.1-3 parts by weight, preferably 0.1-0.6 parts by weight.

[0075] Further, the antioxidant can be a combination of one or more of a hindered phenol antioxidant and a phosphate antioxidant, including but not limited to a combination of one or more of the following compounds: β-[3,5-di-tert-butyl-4-hydroxyphenyl] propionate, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, bis(3,5-di-tert-butyl-4-hydroxypropionyl)hydrazine, 2,2'-oxalyl-bis[ethyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)] propionate, N,N'-hexamethylenebis[[[[[[[[[[[[[[[[[[[[[[[[[[ (3,5-di-tert-butyl-4-hydroxyphenylpropionamide), 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)trione, triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate], 4,6-bis(octylthiomethyl)-o-cresol, tris[2,4-di-tert-butylphenyl]phosphite, bis[2,4-di-tert-butylphenyl]pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate. Based on 100 parts by weight of the ethylene / α-olefin copolymer, the amount of the antioxidant can be 0.01-1 parts by weight, preferably 0.05-0.5 parts by weight.

[0076] In some embodiments, the solar cell encapsulation film composition, based on 100 parts by weight of ethylene / α-olefin copolymer, also includes 0.1-5 parts by weight of a cross-linking agent, preferably 0.5-2 parts by weight; 0.1-5 parts by weight of a co-cross-linking agent, preferably 0.1-2 parts by weight; 0.1-3 parts by weight of a coupling agent, preferably 0.1-0.6 parts by weight; and 0.01-1 parts by weight of an antioxidant, preferably 0.05-0.5 parts by weight.

[0077] The present invention also provides a solar cell encapsulation film, which is prepared using the composition described above. Specifically, the composition contains the ethylene / α-olefin copolymer for photovoltaic encapsulation film provided by the present invention, and the ethylene / α-olefin copolymer satisfies the following conditions (a) to (c) at the same time:

[0078] (a) under the condition of angular frequency of 0.1-500 rad / s, the characteristic relaxation time at 190°C is 200-500 milliseconds, preferably 350.0-500.0 milliseconds, more preferably 400-500 milliseconds;

[0079] (b) a weight average molecular weight of 20,000 to 200,000 g / mol and a density of 0.850 g / cc to 0.910 g / cc;

[0080] (c) Molecular weight distribution is 1.5-3.

[0081] The specific details about the composition and the ethylene / α-olefin copolymer can be referred to the above description and will not be repeated here.

[0082] The present invention also provides a method for preparing the solar cell encapsulation film described above, which comprises the following steps: mixing and melting the components in the composition, extruding and casting into a film, and then cooling and slitting. Specifically, a winding process may also be included. The specific process operation and process conditions of the preparation method can be carried out with reference to conventional methods in the art, and there is no particular limitation on this.

[0083] The solar cell encapsulation adhesive film prepared based on the ethylene / α-olefin copolymer for photovoltaic encapsulation adhesive film of the present invention can take into account both a faster vulcanization reaction speed and good anti-PID performance.

[0084] The present invention also provides a solar cell assembly, which includes the solar cell encapsulation film mentioned above.

[0085] The present invention finds that for ethylene / α-olefin copolymers with a larger characteristic relaxation time, the chain entanglement degree is larger, and compared with ethylene / α-olefin copolymers with a smaller characteristic relaxation time, it is easier to form a body cross-linked structure in the cross-linking reaction, thereby helping to accelerate the vulcanization cross-linking reaction, shorten the time for downstream film factories to use laminators for processing during the application of photovoltaic films, and shorten the time required for the polyolefin elastomer in the film to undergo vulcanization cross-linking reactions. At the same time, the chain entanglement degree in the polyolefin elastomer structure increases, and the film is more likely to form a denser cross-linked structure, thereby enhancing the barrier ability of the encapsulation film to metal ions, reducing the speed at which metal ions migrate to the surface of the battery cell, and thus achieving the effect of improving the anti-PID performance of the photovoltaic encapsulation film.

[0086] The ethylene / α-olefin copolymer for photovoltaic encapsulation film provided by the present invention is an ethylene / α-olefin copolymer with a high characteristic relaxation time, which satisfies conditions (a)-(c) at the same time; the encapsulation film containing the copolymer can take into account both a fast vulcanization reaction speed and good anti-PID performance, and can be widely used in the electrical and electronic industries.

[0087] The present invention will be described in more detail below with reference to examples. The examples provided are only for illustrative purposes and should not be construed as limiting the scope of the present invention.

[0088] The main raw materials are described as follows:

[0089] Tert-butyl peroxy 2-ethylhexyl carbonate, Akzo Nobel, purity > 95%;

[0090] Triallyl isocyanurate, Acros, purity 98%;

[0091] γ-Methacryloxypropyltrimethoxysilane, Aladdin, purity 95%;

[0092] γ-(2,3-Epoxypropyl)propyltrimethoxysilane, Aladdin, purity 95%;

[0093] Bis[2,4-di-tert-butylphenyl]pentaerythritol diphosphite, Acros, purity 95%;

[0094] β-[3,5-di-tert-butyl-4-hydroxyphenyl]propionate, ark, purity 95%;

[0095] 1,1-Bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, Acros, purity 95%;

[0096] Tert-amyl peroxycarbonate, ark, purity 95%;

[0097] Trimethylolpropane triacrylate, Aladdin, purity 98%;

[0098] Antioxidant 1076, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, Li'anlong New Materials Co., Ltd., industrial grade;

[0099] Antioxidant 1010, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, Lianlong New Materials Co., Ltd., industrial grade;

[0100] 1-Octene, Aladdin, purity 99%;

[0101] 1-Butene, Aladdin, purity 99%;

[0102] 1-Hexene, Aladdin, purity 99%;

[0103] 1-Decene, Aladdin, purity 99%;

[0104] Ethylene, open torch gas, purity 99.99%;

[0105] Methylaluminoxane, Akzo, 10%wt toluene solution;

[0106] Modified methylaluminoxane (MMAO-3A), Nouryon, 7wt% solution in toluene.

[0107] Dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride, Jiangsu Xinnoko Catalyst Co., Ltd., purity 98%;

[0108] Dimethylsilyl tert-butylamine tetramethylcyclopentadiene titanium dichloride, Suzhou Yuanqi Material Technology Co., Ltd., purity 98%;

[0109] Bis(methylcyclopentadienyl)zirconium dichloride, Shanghai Mairui Biochemical Technology Co., Ltd., purity 97%;

[0110] Bis(1,3-dimethylcyclopentadienyl)zirconium dichloride, Baoji Funokang Industrial Co., Ltd., purity>95%;

[0111] n-Heptane, Shanghai Aladdin Biochemical Technology Co., Ltd., purity >99.5%;

[0112] n-Octane, Shanghai Aladdin Biochemical Technology Co., Ltd., purity >99.5%;

[0113] Methylhexanophenone, Jinan Hongli Chemical Co., Ltd., purity>99%;

[0114] Bicyclo[3.3.1]nonane-3,7-dione, Zhengzhou Huiju Chemical Co., Ltd., purity 98%;

[0115] 3-Methyl-2-octanone, Shanghai Haohong Biopharmaceutical Technology Co., Ltd., purity>98%;

[0116] 1-phenyl-2,4-pentanedione, Beijing Coupling Technology Co., Ltd., purity>98%;

[0117] Alkane solvent, Tianjin Tairong, industrial grade;

[0118] Ethanol, Tianjin Tairong, industrial grade;

[0119] PERC cells, Tongwei 182 bifacial cells.

[0120] Instruments, devices and testing methods:

[0121] The extruder is a single-screw extruder (L / D=35) with a screw diameter of 30 mm;

[0122] Characteristic relaxation time tester: ARES-G2 rheometer from TA. At 190°C, angular frequencies of 0.1 rad / s to 500 rad / s and a strain of 5%, the complex viscosity was obtained according to the change of stress of the copolymer with the angular frequency, and the characteristic relaxation time λ was calculated by fitting using the following Carreau-Yasuda equation.

[0123]

[0124] η(γ): viscosity, unit: Pa·s

[0125] η ∞ : Infinite viscosity, unit: Pa·s

[0126] η 0 : Zero shear viscosity, unit: Pa·s

[0127] λ: relaxation time, unit: s

[0128] γ: shear rate, unit: s -1

[0129] α: material constant, a dimensionless parameter describing the transition of viscosity from the Newtonian region to the non-Newtonian region. For the Carreau model, α=2;

[0130] n: shear thinning index.

[0131] PID aging equipment: Shanghai Zhiwei environmental chamber, model EW-EC03PID02-021220.

[0132] PID performance test: The prepared double-glass photovoltaic modules were subjected to an anti-PID performance test under the conditions of 96h-85℃ / 85RH / -1500V;

[0133] PID power test equipment used to test anti-PID attenuation: Nanjing Lixit, model LXT-CELL;

[0134] Characteristic vulcanization time Ts1, Ts2 test: using a rotorless vulcanizer, Alpha, MDR; under the conditions of 145°C and 15 min, the characteristic vulcanization time Ts1, Ts2 of the copolymer was tested.

[0135] Melt index of copolymer: measured by melt index meter (CEAST melt index meter, Italy) using the national standard GB / T 3682.1-2018 method, at 190°C and 2.16 kg load, weigh the mass of the extrudate every 6 seconds, perform 5 parallel operations, take the average value and convert it to the mass of the extrudate every 10 minutes, expressed in g / 10min.

[0136] The weight average molecular weight (M w ) and molecular weight distribution (PDI): obtained by high temperature gel permeation chromatography (GPC, Agilent PL-GPC 220, USA). The sample dissolution temperature was 160°C, the mobile phase was 1,2,4-trichlorobenzene containing 500 ppm BHT (2,6-di-tert-butyl-p-cresol), and the flow rate was 1 mL / min. The K value was 1.016×10 -4 , monodisperse polystyrene standard with α value of 0.7220 (M w The K and α values ​​of ethylene / α-olefin copolymer (test sample) were 4.416×10 -4 and 0.7250.

[0137] Density of copolymer: measured by a densitometer (METTLER TOLEDO densitometer) according to ASTM-D792.

[0138] Preparation of ethylene / α-olefin copolymers:

[0139] Preparation of ethylene-octene copolymer A: In a 2.0 L continuous process reactor, hexane solvent was injected at 4.50 kg / h, 1-octene was injected at 2.91 kg / h, and the reactor temperature was controlled at 150°C. At the same time, dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride (0.35 μmol / min, main catalyst) and a toluene solution of 10 wt% methylaluminoxane (3.5 μmol / min, co-catalyst) were injected into the reactor. Then, 1.38 kg / h of ethylene was introduced into the reactor, and the reactor was operated continuously under the condition of controlling the pressure to 60 bar. After the operation was stable (the system temperature and pressure were stable), the reaction solution was continuously taken for about 2 hours, and the solvent in the reaction solution was removed by evaporation to obtain a polymer product.

[0140] The obtained polymer product was completely dissolved in n-heptane solvent under stirring at 80°C to obtain a polymer solution, wherein the mass ratio of the polymer product to the solvent was 1:5; after the temperature dropped to room temperature, the polymer solution was added dropwise into ethanol while stirring, wherein the mass ratio of the polymer solution to ethanol was 1:1. Precipitation was precipitated during the addition process, and after the addition was completed, the liquid phase was evaporated to remove the solvent, and dried in a vacuum oven at 60°C to constant weight to obtain ethylene-octene copolymer A, and the characteristic relaxation time was measured to be 492.2 milliseconds.

[0141] Preparation of Ethylene-Octene Copolymer B: The preparation process is carried out in accordance with that of Ethylene-Octene Copolymer A, except that the precipitate obtained by dropping the polymer solution in ethanol is taken out, and the precipitate is stirred at 80°C until it is completely dissolved in n-heptane, wherein the mass ratio of the precipitate to n-heptane is 1:6, and after the temperature drops to room temperature, the obtained solution is added dropwise to a mixed solvent of ethanol and methyl phenyl ketone in a mass ratio of 6:1 and stirred at the same time, wherein the mass ratio of the solution to the mixed solvent is 1:1. After the dropwise addition is completed, the liquid phase is taken to evaporate and remove the solvent, and dried in a vacuum oven at 60°C to constant weight to obtain Ethylene-Octene Copolymer B, and the characteristic relaxation time is measured to be 210.3 milliseconds.

[0142] Preparation of ethylene-butene copolymer C: In a 2.0 L continuous process reactor, n-octane solvent was injected at 5.0 kg / h, 1-butene was injected at 2.67 kg / h, and the reactor temperature was controlled at 146°C. At the same time, dimethylsilyl tert-butylamine tetramethylcyclopentadiene titanium dichloride (0.48 μmol / min, main catalyst) and a 10 wt% toluene solution of methylaluminoxane (48 μmol / min, co-catalyst) were injected into the reactor. Then, 1.55 kg / h of ethylene was introduced into the reactor, and the reactor was operated continuously under the condition of controlling the pressure to 40 bar. After the operation was stable (the system temperature and pressure were stable), the reaction solution was continuously taken for about 2 hours, and the solvent in the reaction solution was removed by flash evaporation to obtain a polymerization product.

[0143] The obtained polymer product was completely dissolved in n-heptane solvent under stirring at 100°C to obtain a polymer solution, wherein the mass ratio of the polymer product to the solvent was 1:5; after the temperature dropped to room temperature, the polymer solution was added dropwise into ethanol while stirring, wherein the mass ratio of the polymer solution to ethanol was 1:1. Precipitation was precipitated during the addition process, and after the addition was completed, the liquid phase was partially evaporated to remove the solvent, and dried in a vacuum oven at 60°C to constant weight to obtain ethylene-butene copolymer C, and the characteristic relaxation time was measured to be 387.5 milliseconds.

[0144] Preparation of ethylene-butene copolymer D: The preparation process is carried out in accordance with ethylene-butene copolymer C, except that the precipitate obtained by dropping the polymer solution in ethanol is taken out, and the precipitate is completely dissolved in n-heptane at 120°C under stirring, and the mass ratio of the precipitate to the n-heptane is 1:5. After the temperature is lowered to room temperature, the obtained solution is added dropwise to a mixed solvent of ethanol and 3-methyl-2-octanone in a mass ratio of 8:1 and stirred at the same time, wherein the mass ratio of the solution to the mixed solvent is 1:2. After the dropwise addition is completed, the liquid phase is taken to remove the solvent, and dried in a vacuum oven at 60°C to constant weight to obtain ethylene-butene copolymer D, and the characteristic relaxation time is measured to be 240.4 milliseconds.

[0145] Preparation of ethylene-hexene copolymer E: In a 2L intermittent reactor, the temperature was raised to 160°C by an oil bath, and a vacuum pump was connected to the reactor pipeline to remove water vapor and oxygen. After 2 hours, the stirring speed was set to 500rpm, 800mL of n-heptane and 300ml of 1-hexene were added and stirred at 80°C, and bis(methylcyclopentadiene) zirconium dichloride (4μmol) and 2mol / L toluene solution of methylaluminoxane (2mL) were added to the reactant solution while stirring. Ethylene was introduced into the reactor until the pressure stabilized at 4MPa. After 10 minutes of polymerization, the ethylene pressure was released and the solvent was removed by vacuum to obtain a polymer product.

[0146] The obtained polymer product was stirred and mixed with n-heptane at 80°C until the polymer product was completely dissolved, wherein the mass ratio of the polymer product to n-heptane was 1:5; after the temperature dropped to room temperature, the obtained polymer solution was dripped into ethanol while stirring, wherein the mass ratio of the polymer solution to ethanol was 1:1. Precipitation was precipitated during the dripping process, and after the dripping was completed, the liquid phase was taken to remove the solvent, and then dried in a vacuum oven at 60°C to constant weight to obtain ethylene-hexene copolymer E, and the characteristic relaxation time was measured to be 320.1 milliseconds.

[0147] Preparation of ethylene-hexene copolymer F: The preparation process is carried out in accordance with ethylene-hexene copolymer E, except that the precipitate obtained by dropping the polymer solution in ethanol is taken out, and the precipitate is stirred and mixed with n-heptane at 80°C until the precipitate is completely dissolved, wherein the mass ratio of the precipitate to n-heptane is 1:6, and after the temperature drops to room temperature, the obtained dissolved solution is added dropwise to a mixed solvent of ethanol and 1-phenyl-2,4-pentanedione in a mass ratio of 7:1 and stirred at the same time, wherein the mass ratio of the dissolved solution to the mixed solvent is 1:1. After the dropwise addition is completed, the liquid phase is taken to remove the solvent, and dried to constant weight at 60°C in a vacuum oven to obtain ethylene-hexene copolymer F, and the characteristic relaxation time is measured to be 202.8 milliseconds.

[0148] Preparation of ethylene-decene copolymer G: In a 20 L continuous circulation tubular reactor, toluene solvent was injected at 40 kg / h, 1-decene was injected at 20 kg / h, and the reactor temperature was controlled at 126°C. At the same time, bis(1,3-dimethylcyclopentadienyl)zirconium dichloride (5.0 μmol / min, main catalyst) and a toluene solution of 7 wt% Al-modified methylaluminoxane (Nouryon, MMAO-3A) (200 μmol / min, co-catalyst) were injected into the reactor. Then, ethylene was introduced into the reactor at 18.5 kg / h, and the reactor was operated continuously under the condition of controlling the pressure at 45 bar. After the operation was stable (the system temperature and pressure were stable), the reaction solution was continuously taken for about 0.5 h, and the solvent in the reaction solution was removed by flash evaporation and screw extruder to obtain a polymerization product.

[0149] The obtained polymer product was completely dissolved in n-heptane solvent under stirring at 140°C to obtain a polymer solution, wherein the mass ratio of the polymer product to the solvent was 1:4; after the temperature dropped to room temperature, the polymer solution was dripped into ethanol while stirring, wherein the mass ratio of the polymer solution to ethanol was 1:3, and a precipitate was precipitated during the dripping process. After the dripping was completed, the liquid phase was taken to remove the solvent, and dried in a vacuum oven at 60°C to constant weight to obtain ethylene-decene copolymer G, and the characteristic relaxation time was measured to be 498.8 milliseconds.

[0150] Preparation of ethylene-decene copolymer H: The preparation process is carried out in accordance with ethylene-decene copolymer G, except that the precipitate obtained by dropping the polymer solution into ethanol is taken out, and the precipitate is stirred and mixed with n-heptane at 80°C until the precipitate is completely dissolved, wherein the mass ratio of the precipitate to n-heptane is 1:4, and after the temperature drops to room temperature, the obtained solution is dropped into a mixed solvent of ethanol and bicyclo[3.3.1]nonane-3,7-dione at a mass ratio of 6:1 and stirred at the same time, wherein the mass ratio of the solution to the mixed solvent is 1:1. After the dropwise addition is completed, the liquid phase is taken to remove the solvent, and dried in a vacuum oven at 60°C to constant weight to obtain ethylene-decene copolymer H, and the characteristic relaxation time is measured to be 287.6 milliseconds.

[0151] Preparation of ethylene-octene copolymer I: prepared according to the method of comparative example 6 of patent CN113767118B.

[0152] Preparation of ethylene-hexene copolymer J: prepared according to the method of Example 8 of patent US10975173B2.

[0153] The physical properties of the prepared ethylene / α-olefin copolymer are shown in Table 1.

[0154]

[0155] Example 1

[0156] To 1000 g of ethylene-octene copolymer A (ethylene / α-olefin copolymer) were added 9 g of tert-butyl peroxy-2-ethylhexyl carbonate, 5 g of triallyl isocyanurate, 2 g of γ-methacryloxypropyltrimethoxysilane, 1 g of γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, 1 g of bis[2,4-di-tert-butylphenyl]pentaerythritol diphosphite and 1 g of β-[3,5-di-tert-butyl-4-hydroxyphenyl]propionic acid n-octadecyl ester.

[0157] The above raw materials were heated to 50°C and mixed evenly, and the extruder parameters were adjusted, and the temperature from the feed port to the die head was 80°C, 90°C, 90°C, 90°C, 90°C, 95°C, 95°C, 95°C, the screw speed was 45rpm, the traction speed was 0.7rpm, and the winding speed was 1.3rpm. After extrusion, cast film, cooling, slitting and winding, a solar cell encapsulation film was prepared with a film thickness of 0.6mm. Subsequently, tempered glass, encapsulation film, crystalline silicon cell, encapsulation film and float glass were placed in order from top to bottom, and laminated at 145°C by a laminator to obtain a double-glass photovoltaic module.

[0158] Example 2

[0159] To 1000 g of ethylene-octene copolymer B (ethylene / α-olefin copolymer) were added 9 g of tert-butyl peroxy-2-ethylhexyl carbonate, 5 g of triallyl isocyanurate, 2 g of γ-methacryloxypropyltrimethoxysilane, 1 g of γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, 1 g of bis[2,4-di-tert-butylphenyl]pentaerythritol diphosphite and 1 g of β-[3,5-di-tert-butyl-4-hydroxyphenyl]propionate.

[0160] The above raw materials were heated to 50°C and mixed evenly, and the extruder parameters were adjusted, and the temperature from the feed port to the die head was 80°C, 90°C, 90°C, 90°C, 90°C, 95°C, 95°C, 95°C, the screw speed was 45rpm, the traction speed was 0.7rpm, and the winding speed was 1.3rpm. After extrusion, cast film, cooling, slitting and winding, a solar cell encapsulation film was prepared with a film thickness of 0.6mm. Subsequently, tempered glass, encapsulation film, crystalline silicon cell, encapsulation film and float glass were placed in order from top to bottom, and laminated at 145°C by a laminator to obtain a double-glass photovoltaic module.

[0161] Example 3

[0162] To 1000 g of ethylene-butene copolymer C were added 6 g of 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 2 g of tert-amyl peroxycarbonate, 4 g of trimethylolpropane triacrylate, 2 g of γ-methacryloxypropyltrimethoxysilane, 1 g of γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, 0.1 g of antioxidant 1076 and 1 g of antioxidant 1010.

[0163] The above raw materials were heated to 50°C and mixed evenly, and the extruder parameters were adjusted, the temperature from the feed port to the die head was 80°C, 90°C, 90°C, 90°C, 95°C, 95°C, 95°C, the screw speed was 45rpm, the traction speed was 0.7 rpm, and the winding speed was 1.3rpm. After extrusion, cast film, cooling, slitting and winding, a solar cell encapsulation film was prepared with a film thickness of 0.6mm. Then, tempered glass, encapsulation film, crystalline silicon cell, encapsulation film and float glass were placed in order from top to bottom, and laminated at 145°C by a laminator to obtain a double-glass photovoltaic module.

[0164] Example 4

[0165] To 1000 g of ethylene-butene copolymer D were added 6 g of 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 2 g of tert-amyl peroxycarbonate, 4 g of trimethylolpropane triacrylate, 2 g of γ-methacryloxypropyltrimethoxysilane, 1 g of γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, 0.1 g of antioxidant 1076 and 1 g of antioxidant 1010.

[0166] The above raw materials were heated to 50°C and mixed evenly, and the extruder parameters were adjusted, the temperature from the feed port to the die head was 80°C, 90°C, 90°C, 90°C, 95°C, 95°C, 95°C, the screw speed was 45rpm, the traction speed was 0.7 rpm, and the winding speed was 1.3rpm. After extrusion, cast film, cooling, slitting and winding, a solar cell encapsulation film was prepared with a film thickness of 0.6mm. Then, tempered glass, encapsulation film, crystalline silicon cell, encapsulation film and float glass were placed in order from top to bottom, and laminated at 145°C by a laminator to obtain a double-glass photovoltaic module.

[0167] Example 5

[0168] The same method is carried out as in Example 1, except that the ethylene / α-olefin copolymer used is 1000 g of ethylene-hexene copolymer E.

[0169] Example 6

[0170] The same method is carried out as in Example 1, except that the ethylene / α-olefin copolymer used is 1000 g of ethylene-hexene copolymer F.

[0171] Example 7

[0172] The same method is carried out as in Example 3, except that the ethylene / α-olefin copolymer used is 1000 g of ethylene-decene copolymer G.

[0173] Example 8

[0174] The same method is carried out as in Example 3, except that the ethylene / α-olefin copolymer used is 1000 g of ethylene-decene copolymer H.

[0175] Comparative Example 1

[0176] To 1000 g of ethylene-butene copolymer I were added 6 g of 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 2 g of tert-amyl peroxycarbonate, 4 g of trimethylolpropane triacrylate, 2 g of γ-methacryloxypropyltrimethoxysilane, 1 g of γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, 0.1 g of antioxidant 1076 and 1 g of antioxidant 1010.

[0177] The above raw materials were heated to 50°C and mixed evenly, and the extruder parameters were adjusted, the temperature from the feed port to the die head was 80°C, 90°C, 90°C, 90°C, 95°C, 95°C, 95°C, the screw speed was 45rpm, the traction speed was 0.7 rpm, and the winding speed was 1.3rpm. After extrusion, cast film, cooling, slitting and winding, a solar cell encapsulation film was prepared with a film thickness of 0.6mm. Then, tempered glass, encapsulation film, crystalline silicon cell, encapsulation film and float glass were placed in order from top to bottom, and laminated at 145°C by a laminator to obtain a double-glass photovoltaic module.

[0178] Comparative Example 2

[0179] To 1000 g of ethylene-hexene copolymer J were added 6 g of 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 2 g of tert-amyl peroxycarbonate, 4 g of trimethylolpropane triacrylate, 2 g of γ-methacryloxypropyltrimethoxysilane, 1 g of γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, 0.1 g of antioxidant 1076 and 1 g of antioxidant 1010.

[0180] The above raw materials were heated to 55°C and mixed evenly, and the extruder parameters were adjusted, and the temperature from the feed port to the die head was 95°C, 105°C, 105°C, 105°C, 105°C, 105°C, 105°C, 105°C, 105°C, the screw speed was 42rpm, the traction speed was 0.6 rpm, and the winding speed was 1.2 rpm. After extrusion, cast film, cooling, slitting and winding, a solar cell encapsulation film with a film thickness of 0.6mm was prepared. Subsequently, tempered glass, encapsulation film, crystalline silicon cell, encapsulation film, and float glass were placed in order from top to bottom, and laminated at 145°C by a laminator to obtain a double-glass photovoltaic module.

[0181] See Table 2 for the test results of the embodiments and comparative examples.

[0182]

[0183] The experimental results in Table 2 confirm that the ethylene / α-olefin copolymer for solar cell encapsulation film of the present invention can significantly shorten the vulcanization time of the encapsulation film compared with the ethylene / α-olefin copolymer used in the comparative example, while achieving good anti-PID performance. The ethylene / α-olefin copolymer used in the comparative example does not simultaneously meet the conditions (a)-(c) required by the present invention, and the prepared encapsulation film is difficult to achieve both a shorter vulcanization time and good anti-PID performance, and a good balance between the two cannot be achieved.

[0184] The present invention provides an ethylene / alpha-olefin copolymer and a composition thereof for solar cell encapsulation film, wherein the matrix resin has the characteristic of high characteristic relaxation time, making the molecular structure more prone to chain entanglement. When the molecular chain lengths are similar, the degree of chain entanglement of the polymer itself increases, and it is easier to form a body cross-linked structure during the lamination cross-linking reaction, so that the vulcanization cross-linking reaction can be completed faster, shortening the processing time, which is manifested as a decrease in the characteristic vulcanization time Ts1 and Ts2. At the same time, the degree of chain entanglement increases, and the polymer is more likely to form a denser cross-linked structure, thereby enhancing the barrier capacity of the encapsulation film to metal ions, thereby showing the effect of improving the anti-PID effect of the photovoltaic encapsulation film, which is manifested as a decrease in the anti-PID attenuation of the front and back sides of the 96h component. The characteristic relaxation time of the matrix resin used in Comparative Example 1 is too small, and the vulcanization performance of the prepared film and the anti-PID effect of the component are significantly poor. The matrix resin used in Comparative Example 2 has a characteristic relaxation time that is too long, the particles are overall hard, and the density is too high. If the same temperature conditions as in Example 1 are used during the casting process, it is found that it is difficult to completely plasticize the particles, and the temperature needs to be increased additionally to completely plasticize the particles, which will reduce production capacity and is not conducive to downstream subsequent processing. In addition, the particle density is too high, causing the resin particles to be more plastic than elastomer, which makes it difficult for the additives to migrate into the interior of the resin particles during the aging process, making the particle additive absorption effect worse, which is manifested as a serious decrease in vulcanization performance and almost no cross-linking. Furthermore, the particles are overall hard, and the protective effect on the battery cells is weak. The battery cells are prone to hidden cracks during lamination, resulting in a reduction in component yield.

[0185] It is easy to understand that the above embodiments are only examples for clear explanation and do not mean that the present invention is limited thereto. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made on the basis of the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the invention.

Claims

1. An ethylene / α-olefin copolymer for solar cell encapsulation film, characterized in that: The copolymer satisfies the following conditions (a) to (c): (a) The characteristic relaxation time at 190 °C is 350.0–500.0 ms at an angular frequency of 0.1–500 rad / s. (b) a weight average molecular weight of 20,000 to 200,000 g / mol and a density of 0.850 g / cc to 0.910 g / cc; (c) Molecular weight distribution is 1.5-3.

2. The ethylene / α-olefin copolymer according to claim 1, characterized in that The characteristic relaxation time is 400-500 milliseconds.

3. The ethylene / α-olefin copolymer according to claim 1, characterized in that The copolymer has a melt index of 1 g / 10 min to 50 g / 10 min under the conditions of 190° C. and 2.16 kg load.

4. The ethylene / α-olefin copolymer according to any one of claims 1 to 3, characterized in that The weight average molecular weight is 40000-100000 g / mol.

5. The ethylene / α-olefin copolymer according to any one of claims 1 to 3, characterized in that The α-olefin includes one or more of propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene and 1-eicosene.

6. The method for preparing the ethylene / α-olefin copolymer for solar cell encapsulation film according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (S1) polymerizing ethylene and α-olefin to obtain a copolymer product; (S2) post-treating the copolymerization product to separate therefrom an ethylene / α-olefin copolymer that satisfies conditions (a) to (c): (a) The characteristic relaxation time at 190 °C is 350.0–500.0 ms at an angular frequency of 0.1–500 rad / s. (b) a weight average molecular weight of 20,000 to 200,000 g / mol and a density of 0.850 g / cc to 0.910 g / cc; (c) molecular weight distribution is 1.5-3; In step (S2), the post-treatment includes the following step (S2a) and an optional step (S2b): (S2a) dissolving the copolymer product in a first good solvent at 60-140° C., then adding the resulting solution into a first poor solvent for precipitation separation to obtain a first liquid phase, and removing the solvent from the first liquid phase to obtain the desired product; (S2b) dissolving the precipitate obtained by precipitation separation in step (S2a) in a second good solvent at 60-140° C., then adding the obtained solution into a second poor solvent for precipitation separation to obtain a second liquid phase, and removing the solvent from the second liquid phase to obtain the desired product; The first good solvent and the second good solvent are respectively one or more of an aliphatic solvent and an aromatic solvent; The first poor solvent is an alcohol having 2 to 20 carbon atoms; The second poor solvent is a mixed solution of an alcohol solvent and a ketone solvent.

7. The preparation method according to claim 6, characterized in that: The characteristic relaxation time is 400-500 milliseconds.

8. A solar cell encapsulation film composition, characterized in that: The composition comprises the ethylene / α-olefin copolymer described in any one of claims 1 to 5 or the ethylene / α-olefin copolymer prepared by the preparation method described in any one of claims 6 to 7.

9. The solar cell encapsulation film composition according to claim 8, characterized in that: The composition further comprises one or more of a cross-linking agent, a co-cross-linking agent, a coupling agent and an antioxidant.

10. A solar cell encapsulation film, characterized in that: The encapsulation film is prepared by using the composition described in claim 8 or 9.

11. The method for preparing the solar cell encapsulation adhesive film according to claim 10, characterized in that: The steps include: The components in the composition are mixed and melted, extruded and cast into a film, and then cooled and slit.

12. A solar cell assembly comprising the solar cell encapsulation film according to claim 10.

Citation Information

Patent Citations

  • Composition for forming anti-PID packaging adhesive film, anti-PID packaging adhesive film and solar module

    CN112824466A

  • Composition for forming anti-PID packaging adhesive film, anti-PID packaging adhesive film and solar module

    CN112898920A

  • A high PID-resistant encapsulating film and its preparation method

    CN113122164B

  • High-PID-resistance composite packaging adhesive film and preparation method thereof

    CN113234402A

  • Rapid cross-linking packaging material and preparation method and application thereof

    CN115873528A